Spinal Manipulation Therapy for Reducing the Incidence of Low Back Pain among Workers in the Agro-industrial Sector - Femas Agusta Regi Darmawan; Akhmad Ramdhani; Handhias Pramudya Sukma; Enggal Hadi Kurniyawan; Kholid Rosyidi Muhammad Nur; Alfid Tri Afandi; Dicky Endrian Kurniawan (KHD Production, 2025)
Workers in the agro-industrial sector, such as farmers, are very vulnerable to Low Back Pain, because several risk factors cause low back pain in farmers, such as their working position not being in an ergonomic position and being in an extended position at a particular time without any movement or shift in position. Low Back Pain can be very dangerous if not treated immediately, as it can cause adverse effects for the sufferer. One of the methods that can be used in overcoming Low Back Pain in farmers is Spinal Manipulation therapy. This therapy focuses on improving the spine's position and restoring its function to what it was before. This study aimed to determine whether Spinal Manipulation Therapy can reduce the incidence of LBP in farmers in the Agroindustry area. The method used was a literature review using journals as reference sources accessed from Google Scholar, PubMed, and ScienceDirect with keywords